2014
DOI: 10.3389/fnbot.2014.00014
|View full text |Cite
|
Sign up to set email alerts
|

Time changes with feeling of speed: an embodied perspective

Abstract: The speed of moving stimuli can bias duration perception. Here, we investigated whether words describing different speeds influence subjective duration estimation in a temporal bisection task. Duration estimations of two different types of speed words (fast– vs. slow–speed words) were compared. We found that the time bisection point was significantly lower for fast-speed words than for slow-speed words, suggesting that the durations of fast-speed words were overestimated compared to the slow-speed words. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 34 publications
2
33
2
Order By: Relevance
“…In addition, an alternative account for our findings was the embodied perspective, which insists that metaphors in language not only are used for communication but also represent the internal perceptual information (Barsalou, 2008 ; Sun et al, 2011 ; Zhang et al, 2014 ). Indeed, Nather et al ( 2011 ) indicated that the duration of the posture requiring more movement was perceived longer than the posture requiring less movement.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, an alternative account for our findings was the embodied perspective, which insists that metaphors in language not only are used for communication but also represent the internal perceptual information (Barsalou, 2008 ; Sun et al, 2011 ; Zhang et al, 2014 ). Indeed, Nather et al ( 2011 ) indicated that the duration of the posture requiring more movement was perceived longer than the posture requiring less movement.…”
Section: Discussionmentioning
confidence: 93%
“…Studies involving individuals who suffer from attention deficit hyperactivity disorder, depression, schizophrenia and/or Parkinson’s disease (PD) have revealed that individuals with such conditions often have an impaired time perception. 9 Interest in this area has resulted in the development of several models that were specifically designed to define how the central nervous system analyzes and encodes time perception. These models enable a better understanding of some of the phenomena associated with time, such as those relating to memory and attention.…”
Section: Introductionmentioning
confidence: 99%
“…The first two papers (Schreuder et al, 2014 ; Wackermann et al, 2014 ) demonstrated that the judgment of time is systematically distorted with high-arousal/unpleasant emotional stimuli being judged longer than neutral stimuli or low-arousal/pleasant stimuli. In the same line, Zhang et al ( 2014 ) showed that the presentation of Chinese words associated with fast (i.e., galloping, rapid) vs. slow (i.e., gradual) speed produced a lengthening effect in time bisection with the duration of the fast-speed words being judged to last longer than that of the slow-speed words. In addition, Droit-Volet ( 2013 ) showed that this lengthening effect is not specific to time judgment.…”
Section: Psychology and Embodied Cognitionmentioning
confidence: 92%